Symptomatic improvement using everolimus in infants with cardiac rhabdomyoma - Bhargavi Dhulipudi; Shweta Bhakru; Saileela Rajan; Vinoth Doraiswamy; Nageswara Rao Koneti (Wolters Kluwer Medknow Publications, 2019)
Background: Cardiac rhabdomyoma (CR) often shows spontaneous regression and needs close follow-up. These tumors may be associated with tuberous sclerosis complex (TSC), caused by the disinhibition of m-TOR protein. Objective: The aim of the study is to observe the efficacy of everolimus in infants with significant CR. Materials and Methods: This is a single-center prospective observational study including infants with significant CR causing either clinical symptoms or obstruction to the blood flow. Everolimus was administered at a dose of 4.5 mg/M2/wk till the symptomatic improvement. Liver and renal function tests were monitored during treatment. Results: There were six cases of suspected CR included in the study. Median age and weight of patients were 5 days (range: 1-90 days) and 3.2 kg (range: 2.2-4.5 kg), respectively. One patient was excluded after surgical excision biopsy during concomitant closure of associated large perimembranous ventricular septal defect confirmed it as a fibroma. The remaining all five cases showed regression of tumor during mean follow-up of 6.1 ± 5.1 months. One child developed varicella infection necessitating temporary discontinuation of medicine during follow-up. One case had sudden death at 4 months of age. Conclusion: Everolimus appears to be useful in selected cases of symptomatic CR. Multicentric studies are needed to determine its safety and efficacy in larger population.